2022
DOI: 10.1590/0004-282x-anp-2021-0149
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia with 5' extracellular nucleotidase-mediated electroacupuncture for neuropathic pain

Abstract: Background: Acupuncture is a treatment for neuropathic pain, but its mechanism remains unclear. Previous studies showed that analgesia was induced in rats with neuropathic pain when their spinal cord adenosine content increased after electroacupuncture (EA); however, the mechanism behind this electroacupuncture-induced increase has not been clarified. Objective: This study aimed to determine the role that ecto-5’-nucleotidase plays in EA-induced analgesia for neuropathic pain. Methods: We performed electroac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Specifically, acupuncture at ST36 can cause a short-term increase in local eATP at the acupoint, and subsequently accelerate ATP hydrolysis by regulating the levels of the Nucleoside triphosphate diphosphohydrolases (NTPDase)-2/3 in the DRG and ecto-5′NT in the spinal cord, and the sequence of hydrolysis is in the following order: "ATP→ADP→AMP→ADO" [ 140 , 141 ]. Eventually, ADO can bind to A1 receptors to affect purinergic signaling, inhibit ATP binding to purinergic P2 receptors, reduce neurotransmission between neurons, and exert analgesic effects [ [142] , [143] , [144] ]. Evidence suggests [ 145 ] that acupuncture at ST36 single point also induces a localized increase in acupoint macrophage elevation, and the acupuncture signal promotes macrophage differentiation to M2 type and reduces the production of M1 type macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, acupuncture at ST36 can cause a short-term increase in local eATP at the acupoint, and subsequently accelerate ATP hydrolysis by regulating the levels of the Nucleoside triphosphate diphosphohydrolases (NTPDase)-2/3 in the DRG and ecto-5′NT in the spinal cord, and the sequence of hydrolysis is in the following order: "ATP→ADP→AMP→ADO" [ 140 , 141 ]. Eventually, ADO can bind to A1 receptors to affect purinergic signaling, inhibit ATP binding to purinergic P2 receptors, reduce neurotransmission between neurons, and exert analgesic effects [ [142] , [143] , [144] ]. Evidence suggests [ 145 ] that acupuncture at ST36 single point also induces a localized increase in acupoint macrophage elevation, and the acupuncture signal promotes macrophage differentiation to M2 type and reduces the production of M1 type macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, such as the study of Luo et al [13] in 2021 were not included, thus updates on this topic are being requested. Moreover, an emerging body of research has reported the potential roles of various acupuncture treatment types, including manual acupuncture [14], electroacupuncture [15], acupotomy [16], and pharmacopuncture [17] in pain and related disorder management. However, to date, none of the previous research has investigated the effect of each specific acupuncture treatment method.…”
Section: Introductionmentioning
confidence: 99%